2010
DOI: 10.1111/j.1751-9004.2010.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Stereotyping Processes: Integration and New Directions

Abstract: Stereotyping is one of the largest and most enduring research areas in social and personality psychology; many of the processes by which stereotypes are formed, maintained, and applied are now well understood. Yet, little is known about the degree to which stereotyping processes apply outside of North American and Western European contexts. This theoretical paper aims to serve as a starting point for researchers interested in the intersection of culture and stereotyping. We review the nascent literature docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 121 publications
(147 reference statements)
1
5
0
Order By: Relevance
“…Our results showed that, although not significant, there was at endency for men to be higher in facial prominence than women across cultures (male vs. female: 9.52 vs. 8.14% for Taiwanese, and male vs. female: 13.98% vs. 11.43% for Americans in Study 1; male vs. female: 7.99% vs. 7.05% for East Asians, and male vs. female: 13.67% vs. 11.63% for Westerners in Study 2), congruent with recent researches demonstrating gender differences in self-posted profile photos in online social network sites (Cooley &R eichart Smith, 2010;Szillis & Stahlberg, 2007). Our findings are thus suggestive of ac rossculturally invariant form of gender stereotype (Williams &S pencer-Rodgers, 2010) and provide evidence that cultural values as well as social gender stereotypes appear to be internalized by individuals and jointly influence their presentation of photographs in cyberspace.…”
Section: Huang and Parksupporting
confidence: 53%
“…Our results showed that, although not significant, there was at endency for men to be higher in facial prominence than women across cultures (male vs. female: 9.52 vs. 8.14% for Taiwanese, and male vs. female: 13.98% vs. 11.43% for Americans in Study 1; male vs. female: 7.99% vs. 7.05% for East Asians, and male vs. female: 13.67% vs. 11.63% for Westerners in Study 2), congruent with recent researches demonstrating gender differences in self-posted profile photos in online social network sites (Cooley &R eichart Smith, 2010;Szillis & Stahlberg, 2007). Our findings are thus suggestive of ac rossculturally invariant form of gender stereotype (Williams &S pencer-Rodgers, 2010) and provide evidence that cultural values as well as social gender stereotypes appear to be internalized by individuals and jointly influence their presentation of photographs in cyberspace.…”
Section: Huang and Parksupporting
confidence: 53%
“…The reason this comparison is (maybe) of less interest to researchers in Eastern countries is an empirical question in and of itself. Perhaps this relative neglect reflects, in a metalevel sense, generally heightened negative views toward older adults in the East; alternatively, it could be an artifact of stereotyping research being largely Western focused (Williams & Spencer-Rodgers, 2010). Nevertheless, our hope is that—particularly given the cited, aging-related issues afflicting the East—a greater number of Eastern researchers will come to take the lead in investigating this timely topic.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, dialectical lay theories could provide insight into the development, application, stability, and transmission of stereotypic knowledge in different cultural groups. For example, East Asians view social groups as more agentic and entitative than do North Americans (Kashima et al, 2004) and readily stereotype in the absence of contextual information (Spencer-Rodgers et al, 2007); however, their stereotypic beliefs might be more flexible and amenable to change (Williams & Spencer-Rodgers, 2010).…”
Section: Social Categorization and Perceptionmentioning
confidence: 99%